Functionalization of SBA-15 with EDTA and its application in removing Ca2+ and Mg2+ ions from hard water - Marques, Vanessa da Silva Bezerra; Santos, Andarair Gomes dos; Leite, Ricardo Henrique de Lima; Santos, Franciso Klebson Gomes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Poor management, changes in drinking parameters and drought subject many parts of the world to survival in the face of shortages of drinking water and the quality of drinking water needs to be assessed for adequate consumption. Hard water can lead to the buildup of mineral deposits in pipes and appliances that use water on a regular basis, affecting the performance and life cycle of these items. In addition, in the presence of soap, fatty acids formed an insoluble precipitate with calcium ions, making foam and cleaning difficult, as well as other problems generated by the high content of Ca2+ and Mg2+ ions present in water. The goal of this paper was to study the removal of Ca2+ and Mg2+ ions using SBA-15, a mesoporous material, functionalized with ethylenediaminetetraacetic acid and compared to its pure matrix. This adsorbent was tested in Ca2+ and Mg2+ ions solution with concentration of 250 mg.L-1 and pH = 9, varying the temperature in 25°C and 50°C. Mesoporous materials were synthesized by hydrothermal method and characterized by TG/DTG (Thermogravimetry and Derivative Thermogravimetry), XRD (X-Ray Diffraction) and BET (Brunauer, Emmett and Teller method). Adsorption results showed removal of up to 50% of the Ca2+ and Mg2+ ions in a short time, approximately 5 min.